Effect of Work Motivation on The Performance of State Civil Services with Organizational Citizenship Behaviors as an Intervening Variables - Asih Handayani; Aris Eddy Sarwono; Edy Suhartono (Enrichment : Journal of Management, 2020)
This study aims to analyze the significance of the effect of (1) work motivation on organizational citizenship behavior (2) work motivation on the performance of state civil servants (3) The effect of organizational citizenship behavior on the performance of state civil servants (4) the role of organizational citizenship behavior in mediating the effect of work motivation on the performance of the state civil apparatus. The location of this research was carried out in the Regional Government of Ponorogo Regency, East Java. The population in this study were all State Civil Servants (ASN) in the SKPD in the region with a total of 624 ASN people. The sampling technique in this study used a proportional random sampling technique. The analysis technique uses multiple linear regression with the classical assumption test. The results of the analysis oncluded that (1) work motivation has an effect on organizational citizenship behavior (2) work motivation has a positive and significant effect on the performance of state civil servants (3) organizational citizenship behavior has a positive and significant effect on employee performance ( 4) organizational citizenship behavior mediates the effect of work motivation on employee performance